Effective Employer Branding: Need for HR to Partner with Marketing - Rani, Dr. Ridhi; Srinivas, Mr. Ved; Singh, Ms. Sadhana; Reddy, Dr. A. Jagan Mohan; Nisa, Dr. M. (The journal of contemporary issues in business and government, 2022)
In contemporary times of today (volatile, uncertain, complex & ambiguous-VUCA environment), with all other resources being available affordable & accessible, it’s the only talented human resources which could provide cutting edge services to the company. Hence every company would be striving for attracting & retaining the talented people. Needless to say an effective employer brand helps in attracting the talent and reduces the recruitment costs, apart from helping the company in retention of employee. Further, it also helps in improving the performance, through reduced absenteeism and improved work performance. Purpose This is an exploratory paper based on secondary resources looking at employer branding (EB), its need and importance. While looking at few instances of successful employer branding, we would like to make out a call for a partnership between HR and marketing in this crucial exercise. Design /methodology This study is exploratory which is based on literature and document review. It has covered empirical and theoretical research and various articles. Contribution/ Originality This paper looks at the concept of EB, its importance in terms of getting the talented workforce, reduced absenteeism, improved performance & retention of its employees. Hitherto, other than few companies, emphasis was on creating product or corporate brand with a view to improve sales and thereby revenue. But in the changed scenario, where all other resources are available; accessible & affordable, with talented human resource providing the much required cutting edge it’s important to build employer brand on corporate brand for attracting Talented Human Resource(THR). Practical Implications The research will be useful for bolstering a strong partnership between the HR Department and Marketing Department so that there is a harmony between the two wings of the company which otherwise often find each other at loggerheads.